Environmental, Social, And Governance (ESG) Disclosure, Intellectual Capital And Firm Value: The Moderating Role Of Financial Performance - Widya Cita Pramesti; Made Sudarma; Abdul Ghofar (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study aims to empirically examine the effect of Environmental, Social, and Governance (ESG) disclosure and intellectual capital on firm value moderated by financial performance. Methodology/approach: This study uses a quantitative approach with a positivism paradigm. The sample in the study was 125 observations from 25 energy sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The data analysis technique in this study uses Hierarchy Regression Analysis through the use of Multiple Regression Analysis and Moderated Regression Analysis (MRA). Findings: The results showed that Environmental, Social, and Governance (ESG) disclosure has no effect on firm value, while intellectual capital has a positive effect on firm value. This study also shows that financial performance is able to moderate by strengthening the relationship between Environmental, Social, and Governance (ESG) disclosure and intellectual capital on firm value. Practical implications: Companies should strengthen and pay more attention to Environmental, Social, and Governance (ESG) disclosure to fulfill the needs of interested parties. Investors should also consider more financial and non-financial information in assessing companies for decision making. Originality/value: This study is a development of previous research that examines separately the effect of Environmental, Social, and Governance (ESG) disclosure and intellectual capital on firm value. This study also adds financial performance variables with Return on Assets measurement as a moderating variable.